2020
DOI: 10.2174/1871523018666190724124214
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Regulates Inflammation and Tumor

Abstract: Progranulin (PGRN) mediates cell cycle progression and cell motility as a pleiotropic growth factor and acts as a universal regulator of cell growth, migration and transformation, cell cycle, wound healing, tumorigenesis, and cytotoxic drug resistance as a secreted glycoprotein. PGRN overexpression can induce the secretion of many inflammatory cytokines, such as IL-8, -6,-10, TNF-α. At the same time, this protein can promote tumor proliferation and the occurrence and development of many related diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 86 publications
0
16
0
1
Order By: Relevance
“…The results of overexpression, knockout and supplementary experiments showed that miR-1246 can target DYRK1A, regulate the GSK-3β-Wnt/β-catenin signaling pathway, and inhibit the EMT of breast cancer cells. In recent years, studies have found that PGRN plays important roles in the proliferation, drug resistance, migration, and invasion of breast cancer, ovarian cancer, liver cancer and other tumors (13,14,36). In addition, serum PGRN levels are related to the treatment, survival and progression of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of overexpression, knockout and supplementary experiments showed that miR-1246 can target DYRK1A, regulate the GSK-3β-Wnt/β-catenin signaling pathway, and inhibit the EMT of breast cancer cells. In recent years, studies have found that PGRN plays important roles in the proliferation, drug resistance, migration, and invasion of breast cancer, ovarian cancer, liver cancer and other tumors (13,14,36). In addition, serum PGRN levels are related to the treatment, survival and progression of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mutated TNF-α can directly lead to cell canceration ( Yang et al, 2018 ). Meanwhile, IL-6, IL-8, IL-1β, and other inflammatory cytokines can promote tumor proliferation and the development of cervical cancer ( Schäfer et al, 2013 ; Liu et al, 2020 ). For example, IL-1β regulates the expression of CCL-2 by activating nuclear factor-κ-gene binding (NF-κB).…”
Section: The Driving Effects Of Microbiome On Cervical Cancermentioning
confidence: 99%
“…In this study, we showed that ICA treatment was significantly upregulated the spleen and thymus index, as well as the levels of ALB in U14 cervical cancer mouse models. Furthermore, several studies have shown that cytokines can have quite an interesting effect on tumor immunity [ 27 , 28 ]. IFN‑γ, a multifunctional small‑molecule soluble protein, is produced by monocytes and lymphocytes [ 29 ], which plays an important role in the antiviral, anti-proliferative, and anti-tumor in cervical cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF‑α, a cytokine naturally synthesized by the macrophages that directly leads to the death of cancer cells [ 32 ]. Meanwhile, the inflammatory cytokines, such as IL-6, IL-8, and IL-1β can promote tumor proliferation and the occurrence and development of cervical cancer [ 28 ]. In our study, we showed that the expression levels of IFN‑γ, IL-2, and TNF‑α were higher in ICA-treated groups than in the CTX group to ameliorate the immune function of mice.…”
Section: Discussionmentioning
confidence: 99%